Theory of games and economic behavior - Von Neumann, John; Morgenstern, Oskar (Princeton : Princeton University, 1953)
This book contains an exposition and various applications of a mathematical theory of games. The applications are of two kinds: On the one hand to games in the proper sense, on the other hand to economic and sociological problems which the authors hoped to show, are best approached from this direction. The authors' major interest is in the economic and sociological direction. Furthermore they aim to primarily show that there is a rigorous approach to these subjects, involving, as they do, questions of parallel or opposite interest, perfect or imperfect information, free rational decision or chance influences.
rpm 15/09/2017
Loans
Keywords: Game theory; Economics, Mathematical